If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(q + 7) = 45 Reorder the terms: 3(7 + q) = 45 (7 * 3 + q * 3) = 45 (21 + 3q) = 45 Solving 21 + 3q = 45 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 3q = 45 + -21 Combine like terms: 21 + -21 = 0 0 + 3q = 45 + -21 3q = 45 + -21 Combine like terms: 45 + -21 = 24 3q = 24 Divide each side by '3'. q = 8 Simplifying q = 8
| 3-4(x+2)=-5+4(x-5) | | 5p-7=18 | | 3x/1/10 | | 2x-7=7x+4 | | lg(x-10)=10 | | 6+5x=6+x | | -99=5y-6 | | 7x=24-5x | | 2+3(x+1)=-2(3x+4) | | 99x=21y | | -12x^2-176x+3200=0 | | -12x^2-176x+420=0 | | 12x^2-176x+3200=0 | | 3(5-2x)=-(x+4) | | 10y^2-12y-10=0 | | 2:x+3:2x-4=20+3:x | | 2/x+3/2x-4=20+3/x | | 2x+32x-4=20+3x | | 2+10*cos(x)=0 | | -4(2x-5)=2(x-7) | | 4x+25-x=4 | | -9=22-x | | m/5=2000 | | x/5=8x/15=600 | | -(x+5)=2x-5(x+3) | | 6x+5-2x=13 | | 8x+5x+2x=56 | | 8x+5x+2x= | | 8x+5x+2=56 | | 4(3y+2)-10y=16 | | 9x-1=17-x | | 9x+3x=-5 |